2006
DOI: 10.1016/j.bbrc.2006.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heme oxygenase-1 on the vulnerability of astrocytes and neurons to hemoglobin

Abstract: The heme oxygenase (HO) enzymes catalyze the rate-limiting step of heme breakdown. Prior studies have demonstrated that the vulnerability of neurons and astrocytes to hemoglobin is modified in cells lacking HO-2, the constitutive isoform. The present study assessed the effect of the inducible isoform, HO-1. Wild-type astrocytes treated for 3-5 days with 3-30 μM hemoglobin sustained no loss of viability, as quantified by LDH and MTT assays. The same treatment resulted in death of 25-50% of HO-1 knockout astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 45 publications
5
37
0
Order By: Relevance
“…This novel finding suggests that hemin toxicity is due to other mechanisms such as membrane cation leakage, or to the breakdown products of hemin. A deeper understanding of hemin metabolism, and the roles of bilirubin and CO may help to elucidate why some studies find the actions of HO beneficial to cells (Benvenisti-Zarom and Regan, 2007;Chen-Roetling and Regan, 2006) while others find it detrimental (Koeppen et al, 2004;Wang and Dore, 2007). Investiga-tions of whether CO or bilirubin mediate hemin toxicity may aid the development of new therapeutic interventions for hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 97%
“…This novel finding suggests that hemin toxicity is due to other mechanisms such as membrane cation leakage, or to the breakdown products of hemin. A deeper understanding of hemin metabolism, and the roles of bilirubin and CO may help to elucidate why some studies find the actions of HO beneficial to cells (Benvenisti-Zarom and Regan, 2007;Chen-Roetling and Regan, 2006) while others find it detrimental (Koeppen et al, 2004;Wang and Dore, 2007). Investiga-tions of whether CO or bilirubin mediate hemin toxicity may aid the development of new therapeutic interventions for hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 97%
“…While this protective mechanism may be highly relevant to neurons and perhaps other cell types (Doré et al, 1999), prior studies in astrocytes have demonstrated that exogenous bilirubin has no effect on heme-mediated oxidative injury (Regan et al, 2000;Chen-Roetling and Regan, 2006). Although bilirubin is clearly a potent antioxidant (Stocker et al, 1987), its efficacy in astrocytes may be specifically limited by two mechanisms: rapid mitochondrial catabolism and rapid export from cells via multi-drug resistance protein-1 (Hansen and Allen, 1997;Gennuso et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the benefit provided by HO in ischemia and trauma models (Doré et al, 1999;Chang et al, 2003), HO-1 knockout astrocytes were more vulnerable to Hb or hemin (Chen-Roetling et al, 2005;Chen-Roetling and Regan, 2006), while increasing astrocyte expression by genetic or pharmacologic means was protective (Teng et al, 2004;. Putative protective mechanisms include the antioxidant effect of bilirubin production (Doré et al, 1999), and also the conversion of a lipid soluble oxidant, hemin, to iron, which is then sequestered in ferritin (Balla et al, 1992).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Bioactivity of Compounds 1-9 Compounds 1-9 were screened against breast (MCF-7), colon (CKCO-1), lung (H-1299) and skin (HT-144) human cancer cell lines using MTT assay 11) and found to exhibit modest cytotoxcity against the aforementioned cell lines. For breast cancer cell lines (MCF-7), the IC 50 values of compounds 1, 2, 3, 4, 5, 6, 7, 8 and 9 were found to be 48, 43, 35, 46, 28, 45, 55, 67 and 42 mM, respectively.…”
mentioning
confidence: 99%